Risiko Kardiovaskular pada Terapi Radiasi: Tinjauan Klinis tentang Penyakit Jantung yang Diinduksi oleh Radiasi - Widhianto, Andre Tegar (Jurnal Klinik dan Riset Kesehatan, 2025)
Radiotherapy, which has become a pivotal part of cancer treatment over the past 50 years, has indeed proven to increase patient cure rates. However, despite its success, radiotherapy also carries inevitable side effects on the cardiovascular system, specifically radiation-induced heart disease (RIHD). RIHD encompasses a variety of heart diseases, including pericardial disease, coronary artery disease, valvular heart disease, conduction system abnormalities, cardiomyopathy, and vascular disease of medium or large vessels. These side effects can result from the direct impact of radiation on the function and structure of the heart or by accelerating the progression of pre-existing cardiovascular diseases, especially in patients with prior cardiovascular risk factors. Scientists have now developed non-invasive methods to detect RIHD. Additionally, various efforts are being made to prevent and minimize RIHD. This review delves deeper into the pathogenesis, clinical manifestations, diagnosis, management, and prevention of RIHD.